Low-cost modular design microscope for measuring fluorescent diamonds - Adam Mazikowski; Babińska, Maria; Marszewska, Marta (Photonics Letters of Poland, 2024)
Nowadays, microscopy is a widely used method for analyzing various materials. In our research, we use a developed two-channel fluorescence microscope to measure objects excited with two different wavelengths, e.g. fluorescent diamond powders with nitrogen vacancies. The results obtained were compared with images illuminated with white LED observed using a microscope in the transmission mode. The measurements yielded results with satisfactory resolution and image quality. Considering that the microscope built is a budget design, so it can be a cheaper alternative to commercial devices. Full Text: PDF References J.C. Stockert, A. Blázquez-Castro, "Fluorescence Microscopy in Life Sciences" Bentham Science Publishers. ISBN 978-1-68108-519-7 (2017). CrossRef W.W. Hsiao, Y.Y. Hui, P.C. Tsai, H.C. Chang, "Fluorescent Nanodiamond: A Versatile Tool for Long-Term Cell Tracking, Super-Resolution Imaging, and Nanoscale Temperature Sensing", Acc. Chem. Res. 49(3), 400 (2016). CrossRef M.B. Amiri Olia, P.S. Donnelly, L.C.L. Hollenberg, P. Mulvaney, D.A. Simpson, "Advances in the Surface Functionalization of Nanodiamonds for Biological Applications: A Review", ACS Appl. Nano Mater. 4(10), 9985 (2021). CrossRef B.S. Miller, et al. Spin-enhanced nanodiamond biosensing for ultrasensitive diagnostics. Nature 587, 588 (2020). CrossRef B.H. Oh, K.H. Kim, K.Y. Chung, "Skin Imaging Using Ultrasound Imaging, Optical Coherence Tomography, Confocal Microscopy, and Two-Photon Microscopy in Cutaneous Oncology", Front. Med., Sec. Dermatology, 6 (2019). CrossRef L. Schmidheini et al. "Self-Assembly of Nanodiamonds and Plasmonic Nanoparticles for Nanoscopy", Biosensors, 12, 148 (2022). CrossRef W. Białobrzeska, et al. "Quantitative fluorescent determination of DNA - Ochratoxin a interactions supported by nitrogen-vacancy rich nanodiamonds", J. Mol. Liq., 342 (2021). CrossRef O.S. Wolfbeis, "Materials for fluorescence-based optical chemical sensors", J. Mater. Chem., 15, 2657 (2005). CrossRef T. Zhang, et al. "Toward Quantitative Bio-sensing with Nitrogen-Vacancy Center in Diamond". ACS Sens., 6, 2077 (2021). CrossRef N. Nunn, M. Torelli, G. McGuire, O. Shenderova. "Nanodiamond: A high impact nanomaterial". Curr. Opin. Solid State Mater. Sci. 21(1), 1 (2017). CrossRef S.J. Yu, M.W. Kang, H.C. Chang, K.M. Chen, Y.C. Yu, "Bright fluorescent nanodiamonds: no photobleaching and low cytotoxicity", J. Am. Chem. Soc. 127(50), 17604 (2005). CrossRef O. Shenderova et al. "Commercial quantities of ultrasmall fluorescent nanodiamonds containing color centers", Proc. SPIE, 10118, 1011803 (2017). CrossRef M.H. Alkahtani et al. "Fluorescent nanodiamonds: past, present, and future". Nanophotonics, 7(8), 1423 (2018). CrossRef M. Głowacki, et al. "Fluorescence of nanodiamond cocktails: pH-induced effects through interactions with comestible liquids", Food chemistry, 381, 132206 (2022). CrossRef Y. Xue, X. Feng, S.C. Roberts, X. Chen, "Diamond and carbon nanostructures for biomedical applications", Functional Diamond, 1(1), 221 (2021). CrossRef A. Nagl, S.R. Hemelaar, R. Schirhagl, "Improving surface and defect center chemistry of fluorescent nanodiamonds for imaging purposes-a review", Anal. Bioanal. Chem., 407, 7521 (2015). CrossRef S. Sengottuvel, et al., "Wide-field magnetometry using nitrogen-vacancy color centers with randomly oriented micro-diamonds", Sci. Rep. 12, 17997 (2022). CrossRef P. Nowicki, E. Czarniewska, "Nanodiamenty: unikalne nanocząsteczki do zastosowania w biomedycynie i biotechnologii", Postępy Biochem., 65(4) (2019). CrossRef S.D Subedi, V.V. Fedorov, J. Peppers, D.V. Martyshkin, S.B. Mirov, L. Shao, M. Loncar, "Laser spectroscopic characterization of negatively charged nitrogen-vacancy (NV−) centers in diamond", Opt. Mater. Express 9, 2076 (2019). CrossRef